Using AI in bioimage analysis to elevate the rate of scientific discovery as a community - Nogare, Damian Dalle; Hartley, Matthew; Deschamps, Joran; Ellenberg, Jan; Jug, Florian (Nature methods, 2023)
The future of bioimage analysis is increasingly defined by the development and use of tools that rely on deep learning and artificial intelligence (AI). For this trend to continue in a way most useful for stimulating scientific progress, it will require our multidisciplinary community to work together, establish FAIR (findable, accessible, interoperable and reusable) data sharing and deliver usable and reproducible analytical tools.